2022
DOI: 10.1037/pha0000451
|View full text |Cite
|
Sign up to set email alerts
|

Episodic future thinking as a brief alcohol intervention for heavy drinking college students: A pilot feasibility study.

Abstract: Episodic future thinking (EFT), an exercise that involves cognitive simulation of future events, has demonstrated proximal effects on alcohol demand and delayed reward discounting (DRD). However, few studies have investigated EFT's potential to reduce alcohol use and increase positive behaviors outside of the laboratory. This study is the first to pilot an academic goal-relevant EFT (A-EFT) intervention for heavy drinking college students. The primary goals were to evaluate the feasibility and acceptability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 95 publications
(147 reference statements)
0
41
2
5
Order By: Relevance
“…First, unlike other studies (see, e.g., Chiou and Wu 2017;Stein et al 2016Stein et al , 2018, this sample consists of treatment-seeking smokers, rather than current smokers without motivation to quit, a variable strongly related to RP (Sheffer et al 2019;Veilleux and Skinner 2016). Second, the number of days of abstinence from substance use was higher (an average of 274.60), compared to previous EFT studies with SUD populations (see, e.g., Forster et al 2021;Sofis et al 2020;Voss et al 2021). These differences in the participant profiles may have an impact on RP.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, unlike other studies (see, e.g., Chiou and Wu 2017;Stein et al 2016Stein et al , 2018, this sample consists of treatment-seeking smokers, rather than current smokers without motivation to quit, a variable strongly related to RP (Sheffer et al 2019;Veilleux and Skinner 2016). Second, the number of days of abstinence from substance use was higher (an average of 274.60), compared to previous EFT studies with SUD populations (see, e.g., Forster et al 2021;Sofis et al 2020;Voss et al 2021). These differences in the participant profiles may have an impact on RP.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with the RP framework, episodic future thinking (EFT) is a novel treatment that consists of imagining future events in order to forego immediate pleasures in pursuit of longer-term aims (Hollis-Hansen et al 2019;Rung and Epstein 2020;Schacter et al 2017). EFT has shown effects on substance use, such as reduction of tobacco use (Chiou and Wu 2017;Stein et al 2016), and reduction of alcohol use (Voss et al 2021). Additionally, in substance users, EFT has been shown to reduce DD rates (Athamneh et al 2021;Bulley and Gullo 2017;Chiou and Wu 2017;Forster et al 2021;Mellis et al 2019;Patel and Amlung 2020;Snider et al 2016;Sofis et al 2020;Stein et al 2016Stein et al , 2018 and drug demand indices (Athamneh et al 2021;Bulley and Gullo 2017;Patel and Amlung 2020;Snider et al 2016Snider et al , 2018Voss et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These findings provide initial evidence that 2 weeks of online training to respond to negative affect drinking triggers by retrieving future adaptive strategies can improve drinking-related outcomes, in hazardous, student, negative affect drinkers. The current study added to the existing literature that imagery retrieval training approach has utility for improving substance use outcomes [25,33,53].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, training individuals to imagine their best possible future self in response to negative affect has been found to improve symptoms of depression and anxiety [20,21]. Similarly, episodic positive future thinking studies have found that instructing participants to think of achieving positive future goals improves mood [22], reduces alcohol demand in college students [23] and alcohol-dependent individuals [24], reduces alcohol consumption and increases the use of protective behaviour strategies (to reduce problematic drinking) in heavy drinking college students [25]. Episodic positive future thinking also reduces food intake [26,27] and promotes weight loss in overweight individuals [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation